Failed methotrexate therapy in a cesarean scar ectopic pregnancy: a case report - Belal, Rania E.; Abbashar, Eman Mohammed; Adam, Acha Assmanni (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Cesarean scar ectopic pregnancy (CSEP) is a rare and potentially life-threatening early pregnancy complication associated with prior cesarean section scars, where early detection and treatment are critical to reducing maternal morbidity. Methotrexate (MTX) therapy is a standard conservative approach, but may fail in some instances. We report a case of a 29-year-old woman (gravida 5, para 4) who presented at seven weeks’ gestation with mild vaginal bleeding. Transvaginal ultrasound (TVUS) confirmed a non-viable CSEP, and ultrasound-guided intra-sac MTX injection was attempted as conservative management. Despite treatment, the patient developed worsening haemorrhage requiring emergency surgical intervention. Intraoperative findings revealed significant vascularity at the implantation site, and surgical excision of the ectopic pregnancy was performed with preservation of the uterus. The postoperative course was uneventful. This case highlights the limitations of MTX in treating CSEP. It emphasizes the importance of early recognition of treatment failure and prompt surgical management to prevent severe maternal morbidity and preserve reproductive potential.